INTRATHYROID THYROGLOSSAL DUCT CYST WITH CHRONIC LYMPHOCYTIC THYROIDITIS IN AN ADULT FILIPINO: A CASE REPORT - David, Edmond; Yao, Hearty; Gomez , Maria Honolina (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Intra-thyroid thyroglossal duct cyst (TDC) in adults is rare. It is even rare for intrathyroidal TDC to present with chronic lymphocytic thyroiditis. We report a case of a 23-year-old Filipino female who presented with a three-year history of recurrent thyroid mass and recurrent aspiration of thyroid cyst. A welldefined, non-tender, firm-hard, movable midline mass was noted on physical examination. On sonogram, a cystic focus with smooth borders and no internal echogenicity extending to the isthmus measuring 2.9 x 3.5 x 1.1 cm was seen. The thyroid function test was normal. She underwent left thyroid lobectomy and isthmectomy revealing a cystic nodule with 7.5 ml purulent discharge. Histopathology showed intra-thyroidal thyroglossal duct cyst and chronic lymphocytic thyroiditis. Most cases of intra-thyroidal TDC present as an anterior neck mass and are diagnosed postoperatively. Proper head and neck examination with radiologic imaging isnecessary to recognize patients who could benefit from more aggressive treatment. Based on the literature, this is the first case reported by an adult Filipino.